Ejectors in Hydrogen Recirculation for PEMFC-Based Systems: A Comprehensive Review of Design, Operation, and Numerical Simulations - Masoud Arabbeiki; Mohsen Mansourkiaei; Domenico Ferrero; Massimo Santarelli (Energies, 2024)
Fuel cell systems often utilize a hydrogen recirculation system to redirect and transport surplus hydrogen back to the anode, which enhances fuel consumption and boosts the efficiency of the fuel cell. Hydrogen recirculation pumps and ejectors are the most investigated systems. Ejectors are gaining recognition as an essential device in fuel cell systems. However, their application in hydrogen recirculation systems is often limited by a narrow operational range. Therefore, it is advantageous to compile the present condition of the study on various ejector shapes as well as configurations that can accommodate a broader operational range, along with the numerical simulations employed in these studies. This paper begins by examining the structure and operation of ejectors. It then compares and analyzes the latest advancements in research on ejector-based hydrogen recirculation systems with extended operating ranges and reviews the details of numerical simulations of ejectors, which are crucial for the development of innovative and efficient ejectors. This study provides key insights and recommendations for integrating hydrogen ejectors into the hydrogen cycle system of fuel cell engines.